Respuesta :
Answer:
g(f(x))=(−3x+7)2−8 (a. -55/7)
Step-by-step explanation:
f(x)=−3x+7g(x)=x2−8g(f(x))=(−3x+7)2−8
and i like you pfp! Hope i helped if wrong tell me.
~Ally
Answer:
- C. 63/55 is the right option.
---- HappY LearninG <3 ------
![Ver imagen TheAnimeGirl](https://us-static.z-dn.net/files/d8a/78c89973ad9dca1918193c1d144c8de9.jpg)
Answer:
g(f(x))=(−3x+7)2−8 (a. -55/7)
Step-by-step explanation:
f(x)=−3x+7g(x)=x2−8g(f(x))=(−3x+7)2−8
and i like you pfp! Hope i helped if wrong tell me.
~Ally
Answer:
---- HappY LearninG <3 ------